An interactive graphical user interface (GUI) for the CATGIXRF program – for microstructural evaluation of thin film and impurity doped surfaces. (22nd March 2016) - Tiwari, M. K.; Das, Gangadhar
Abstract : This paper is a continuation and extension of our earlier work ( X‐ray Spectrom .2010, 39, 127–134, DOI:10.1002/xrs.1215) on the development of a software platform CATGIXRF, as a solution to provide non‐destructive evaluation of nanostructured materials. Here, we describe an interactive graphical user interface (GUI) for the CATGIXRF program. The newly developed GUI interface facilitates determination of microstructural parameters on angstrom length scale for the nanostructured thin layered materials using synchrotron as well as laboratory X‐ray sources. It allows combined analysis capabilities for both the X‐ray reflectivity and grazing incidence X‐ray fluorescence (GIXRF) data simultaneously, thus enabling us a greater sensitivity for the determination of microstructural parameters such as thickness, interface mixing, and roughness of a thin film medium with improved accuracies. The utility and various newly added salient features of the GUI‐CATGIXRF program are described by providing example calculations as well as by analyzing experimentally a few thin film structures with different surface‐interface properties. Copyright © 2016 John Wiley & Sons, Ltd.